Manifestly local theory of vacuum energy sequestering - Kaloper, Nemanja; Padilla, Antonio; Stefanyszyn, David; Zahariade, George (American Physical Society, 2016)
We present a manifestly local, diffeomorphism invariant, and locally Poincaré invariant formulation of vacuum energy sequestering. In this theory, quantum vacuum energy generated by matter loops is canceled by auxiliary fields. The auxiliary fields decouple from gravity almost completely. Their only residual effect is an a priori arbitrary, finite contribution to the curvature of the background geometry, which is radiatively stable. Its value is to be determined by a measurement, like the finite part of any radiatively stable UV-sensitive quantity in quantum field theory.